2014
DOI: 10.1177/1556264614553170
|View full text |Cite
|
Sign up to set email alerts
|

“Protecting” or “Policing”

Abstract: A recent surge of research universities and human subjects research funding in the Arab world raises concerns about applied research ethics and oversight. In-depth interviews conducted with 52 researchers in Lebanon and Qatar about their research conduct and the problems they face while conducting it indicate that although researchers admit to the added value of institutional review board (IRB) functions, the researchers have several complaints, such as rigid and contextually insensitive requirements, delays, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…[19][20][21][22][23][24][25] Adoption of research ethics guidelines and implementation of training on responsible conduct of research (RCR) in the academic and research institution in the region might overcome most of such challenges. 21,26,27 Notably, the current study has shown that previous participation in medical research was correlated with lower overall perception of values and ethics of research, yet, higher trust in research. Such results indicate the need form researchers to improve research experience among medical research participants to leave a more positive perception among them.…”
Section: 4%mentioning
confidence: 52%
“…[19][20][21][22][23][24][25] Adoption of research ethics guidelines and implementation of training on responsible conduct of research (RCR) in the academic and research institution in the region might overcome most of such challenges. 21,26,27 Notably, the current study has shown that previous participation in medical research was correlated with lower overall perception of values and ethics of research, yet, higher trust in research. Such results indicate the need form researchers to improve research experience among medical research participants to leave a more positive perception among them.…”
Section: 4%mentioning
confidence: 52%
“…In their study of two RECs, clinical and non-clinical, at a medical school in Thailand, Adams and colleagues (2014) identified the need for improvement of internal processes. Makhoul and colleagues (2014) also identified areas of concern in their study of RECs in Lebanon and Qatar, specifically with regard to the inadequacy of resources for the REC, poor communication between REC members and researchers, and REC application requirements considered to be overly rigid and insensitive of context. Matar and Silverman (2013) used in-depth semi-structured interviews to assess the functioning of RECs in the Middle East, namely Egypt, and identified themes related to the composition of membership, the training needs of REC members, the need for resources (human and capital), the impact of the national government on REC functioning, and the issues surrounding informed consent, among others.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of competent committees and comprehensive standards for REC functioning in LMICs is highlighted in the literature (Adams et al, 2014; Chenneville et al, 2014; Makhoul et al, 2014; Matar & Silverman, 2013; Silverman, Edwards, Shamoo, & Matar, 2013; Silverman & Sleem, 2014; Silverman et al, 2014). Nonetheless, concerns remain.…”
Section: Introductionmentioning
confidence: 99%
“…In many countries of the region, researchers may encounter barriers related to lacking or inadequate research infrastructures. To the extent that REC and the ethical research principles entrenched in the Belmont Report are rooted in Western research traditions, they may not be intuitive in Arab countries where different social and cultural values and norms are embraced (Makhoul et al, 2014). Anthropological research may be needed to identify how health researchers negotiate the tensions between local practices and global ethical research norms.…”
Section: Discussionmentioning
confidence: 99%